Electrocardiographic modifications and cardiac involvement in COVID-19 patients: results from an Italian cohort. Issue 3 (18th March 2021) - Matteucci, Andrea; Massaro, Gianluca; Sergi, Domenico; Bonanni, Michela; Stifano, Giuseppe; Matino, Matteo; Zerillo, Bartolomeo; Rogliani, Paola; Romeo, Francesco
Abstract : Aim: The aim of this study was to detect predisposing CV risks factors and ECGs changes in COVID-19 patients. Methods: The study population included 60 noncritically ill patients with COVID-19 pneumonia admitted to our hospital between 16 March and 11 May 2020. Electrographic changes, evaluated from ECGs acquired at admission and at 7 days after starting COVID-19 therapy, were analysed. We also compared 45 patients without CV involvement with 15 patients with new onset of cardiac adverse events during hospitalization. Results: ECGs under treatment showed a lower heart rate (HR) (69.45 ± 8.06 vs 80.1 ± 25.1 beats/min, P  = 0, 001) and a longer QRS (102.46 ± 15.08 vs 96.75 ± 17.14, P  = 0.000) and QT corrected (QTc) interval (452.15 ± 37.55 vs 419.9 ± 33.41, P  = 0, 000) duration than ECGs before therapy. Fifteen patients (25%) showed clinical CV involvement. Within this group, female sex, lower ejection fraction (EF), low serum haemoglobin, high Troponin I levels (TnI), low lymphocytes count, high serum IL-6 levels, or use of Tocilizumab (TCZ) were more represented. Conclusions: Patients admitted for SARS-CoV2 infection and treated with anti-COVID-19 drug therapy develop ECG changes such as reduction in HR and increase in QRS duration and QTc interval. One in four patients developed CV events. Gender, EF, heamoglobin values, TnI, lymphocytes count, IL-6 and use of TCZ can be considered as predisposing factors for CV involvement.